Combining manufacturing of titanium alloy through direct energy deposition and laser shock peening processes. (May 2021) - Chi, Jiaxuan; Cai, Zhongyi; Zhang, Hepeng; Zhang, Hongqiang; Guo, Wei; Wan, Zhandong; Han, Guofeng; Peng, Peng; Zeng, Zhi
Abstract: Combined manufacturing of direct energy deposition (DED) and laser shock peening (LSP) exhibits great potentials in repairing titanium alloy components and improving their mechanical properties. In this study, a DEDed repaired sample was fabricated by depositing TA15 powders on a forged TC17 plate, and subjected to a following LSP treatment. The effects of LSP on microstructures, residual stress, and tensile properties of DEDed samples were evaluated. After LSP, a high-level compressive residual stress state (maximum =−596 MPa) and microstructure refinement were induced in the treated surface. The average α phase area decreased from 1.88 μm 2 to 0.73 μm 2, and much more low angle grain boundaries were induced after LSP. Meanwhile, the corresponding ultimate tensile strength (UTS) was improved by 12.46%. Graphical abstract: Unlabelled Image Highlights: Laser shock peening is used on additive manufactured parts to modify microstructure and induce compressive residual stress. High-density dislocation considerably promotes the microhardness and work hardening rate. The ultimate tensile strength is improved by 12.46% after laser shock peening.